Vincenzowska oralność - Ługowska, Jolanta (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
Stanisław Vincenz was remembered by his family, friends and neighbours as a man who throughout his whole life cultivated the art of conversation. He placed a high value on direct contact with hislistener, trying to understand his point of view even when the dialogue was of a confrontational nature and he was associated with a personal threat (Dialogues with the Soviets). He was also dedicated tothe concept of the transfer of knowledge through the spoken word, as was expressed in various types of talks, readings and lectures. In addition, the writer would also find patterns of orality in ancient culture,above all in the Homeric epics, which he knew extremely well and of which he was a passionate reader. The character and patterns of orality and statements characteristic of living speech also shapedhis individuality as a writer when he was making decisions about the language and style of his most important work On the High Pastures. In this composition, which is called the ’Hutsul Tetralogy’ by literaryexperts, the oral culture appears to be both a theme and a form of artistic statement. In respect of its composition Pastures is characterized by a predominance of dialogue and a variety of methods of orationon the story on the parts of the heroes; the story itself is sometimes presented as a mere pretext. In their dialogues the Hutsul heroes of the tetralogy make complex philosophical, theological and politicalenquiries, expound on the topic of education, the sense of inventions by civilization and the meanings of their own tradition. In presenting replicas of the heroes’ dialogues the author focuses not merely onwhat the characters are saying but also on the dialogic setting itself in attempting to take into account the manner and aim of the statements made by each of the protagonists. Vincenz’s fascination withoratorical descriptions is linked with both folkloric tradition, which he knew from his own study, and with the ancient symposium, which is mentioned by, among others, Homer in the Odyssey.
Keywords: Stanisław Vincenz; oralność; komunikacja